Praktik Sistem Kerja Berkinerja Tinggi terhadap Komitmen Afektif dengan Mediasi Keadilan Prosedural - Masrukhin, Muhamad Agus (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2014)
The objective of the study was to test the direct influence of high performance work system toward the affective commitment and indirect influence of high performance work system toward the affective commitment with procedural justice as the mediating variable. It was a survey research by distributing the questionnaires to 93 employees which were taken randomly. The data were analyzed by line analysis. The result of the study showed that high performance work system gave positive and significant influence toward the affective commitment with procedural justice as the mediating variable.